Atomic absorption spectrometry : an introduction - Sanz-Medel, Alfredo; Pereiro, Rosario (Momentum Press, 2014)
We have restricted the scope of this tutorial book to the study of fundamentals and practical use of such popular and efficient atomic absorption techniques. An up-to-date account of AAS fundamentals, instrumentation, special techniques, and elemental analysis applications is provided here. To do so, the atomic absorption experiment and the photophysical law governing such photon absorption processes are revised first. Then, the main components or units, that, when adequately assembled, constitute an AAS instrument, are described in detail to set the foundations of modern spectrometers for AAS measurements.